Two-Sample Mendelian Randomization detects bidirectional causality between gut microbiota and celiac disease in individuals with high genetic risk - González-García, Bárbara P.; Marí, Sergi; Cilleros-Portet, Ariadna; Hernangomez-Laderas, Alba; Fernandez-Jimenez, Nora; García-Santisteban, Iraia; Bilbao, Jose Ramon (Frontiers in Immunology, 2023)
Background: Celiac Disease (CeD) is an autoimmune disorder triggered by gluten intake in genetically susceptible individuals. Highest risk individuals are homozygous for the Human Leucocyte Antigen (HLA) DQ2.5 haplotype DQ2.5/ DQ2.2 heterozygous. Both the HLA DQ2-positive, high genetic risk individuals and those that have developed the disease have altered intestinal microbiota, but it remains unclear whether these alterations are a cause or a consequence of CeD. Objective: To investigate a potential bidirectional causality between gut microbiota (GM) and CeD in HLA DQ2 high genetic risk individuals. Materials and Methods: We performed a bidirectional Two Sample Mendelian Randomization (2SMR) test using summary statistics from the largest publicly available Genome Wide Association Studies (GWAS) of GM and the summary statistics of the Immunochip CeD study of those individuals with the HLA DQ2 high-risk haplotype. To test whether changes in GM composition were causally linked to CeD, GM data were used as exposure and CeD data as outcome; to test for reverse causation, the exposure and outcome datasets were inverted. Results: We identified several bacteria from Ruminococcaceae and Lachnospiraceae families of the Firmicutes phylum as potentially causal in both directions. In addition, our results suggest that changes in the abundance of Veillonellaceae family might be causal in the development of CeD, while alterations in Pasteurellaceae family might be a cons-equence of the disease itself. Conclusion: Our results suggest that the relationship between GM and HLA DQ2 high risk individuals is highly complex and bidirectional.